Grado de competitividad en la Empresa Corpdiseño en la ciudad de guayaquil, periodo 2023. - Arguello Morejón, Evelyn Aracely (2024)
In this case study, it was carried out in the Corpdiseño company in the city of Guayaquil with the purpose of analyzing the degree of competitiveness in the Corpdiseño company in the city of Guayaquil, period 2023, applying research techniques to recommend actions that help improve positioning in the market. To carry out this research, a method with a descriptive design with a qualitative approach was applied, for the collection of information the SWOT technique was used that allowed defining the current situation of the company and the analysis of reality that was complemented with other techniques. support such as the interview carried out by the company's deputy manager and the comparison with the purpose of knowing the company's competitors and their differentiation strategies. In addition, it was reinforced with theoretical bases that involved presenting a set of key concepts, approaches and knowledge from different authors about competitiveness, importance, characteristics, types of competition, factors, among others. Since, it helps to better understand the problem within the company and analyze the results obtained from the applied methodology. Such is the case of the company Corpdiseño, which to continue remaining in the market must apply strategies aimed at its products and services to establish solid relationships with customers by applying a more attractive value proposition.